Republic of Congo : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2004)
This Selected Issues and Statistical Appendix paper outlines the recent developments in the political and security situation in Congo. It reviews economic performance during 1970-2003, including in the context of IMF-supported programs. The paper also reviews recent developments in public finance management, and examines the constraints on growth and poverty reduction. The sources of economic growth during 1970-2003 are analyzed. The paper also discusses the feasibility of an oil fiscal rule, and notes some key lessons and challenges for the Congo.